The Motive Of Wearing A Face Veil In The Early Islam: Two Narratives Of Prophetic Traditions - M., Hasbi; Hasbullah, Hasbullah; Jamaluddin, Jamaluddin (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2018)
This article discusses the motives for wearing a face veil in early Islam. With the lens of prophetic historical reflection, it focuses on two narratives of the hadith on veil: the Arab women who sold in the market of Bani Qaynuqa‘ and ‘Aishah on hadith al-ifk. This article argues that the motives of covering their faces has close related to the situation and conditions occurred at the time. Historically, the two stories explained that wearing a face veil as a protection of dignity and self-esteem from an uncomfortable milieu. Sociologically, the face veil was cultural habits in guarding women from any social disorders and negative treatment. While psychologically, wearing a face veil symbolized the purity of an honor and the high value of personality embedded in the dignity of women so as not to invite a slander.